Religious Obligation and its Relationship to Forgiveness among a Sample of Spouses in the city Sabha (Journal of Human Sciences, 2022)
The current study aims to identify some behavioral deviations as predictors of criminal behavior from the point of view of a sample of psychological counselors in a number of schools in the city of Sebha. The study relied on the descriptive analytical method, and the study sample consisted of (30) psychological counselors.The results concluded that the criminal behavior of the students reaches a relatively average level. There are no statistically significant differences with regard to some behavioral deviations as predictors of criminal behavior. There are statistically significant differences on the scale of behavioral deviations among middle school students according to the variable years of experience, and these differences are in favor of the counsellors. Psychologists whose experience ranged between (16-20), there are no differences on the scale of criminal behavior among middle school students according to the variable years of experience. Age, The study recommends activating the role of the psychological counselor and enhancing and refining his experience to be a positive tributary in luating students’ behavior in schools.